2018
DOI: 10.1016/j.bbamcr.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The uL10 protein, a component of the ribosomal P-stalk, is released from the ribosome in nucleolar stress

Abstract: The ribosomal uL10 protein, formerly known as P0, is an essential element of the ribosomal GTPase-associated center responsible for the interplay with translational factors during various stages of protein synthesis. In eukaryotic cells, uL10 binds two P1/P2 protein heterodimers to form a pentameric P-stalk, described as uL10-(P1-P2), which represents the functional form of these proteins on translating ribosomes. Unlike most ribosomal proteins, which are incorporated into pre-ribosomal particles during early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 83 publications
3
21
0
Order By: Relevance
“…Flow cytometric analyses showed that RNaseA treatment significantly decreased the MFI of TO on platelets from control and patient P1 but only moderately affected this value on platelets from patient P2. Therefore, the high TO staining in P2 platelets as compared to that in control platelets was not due to a higher RNA content, but probably to a greater number of dense granules that contributed to TO fluorescence . In contrast, in P1 platelets the TO staining was partly due to a higher proportion of young platelets, confirming the observed elevated expression of HLA I (Figure D, right panel).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Flow cytometric analyses showed that RNaseA treatment significantly decreased the MFI of TO on platelets from control and patient P1 but only moderately affected this value on platelets from patient P2. Therefore, the high TO staining in P2 platelets as compared to that in control platelets was not due to a higher RNA content, but probably to a greater number of dense granules that contributed to TO fluorescence . In contrast, in P1 platelets the TO staining was partly due to a higher proportion of young platelets, confirming the observed elevated expression of HLA I (Figure D, right panel).…”
Section: Resultssupporting
confidence: 54%
“…Ribosomal P‐antigen is present on the C‐terminal part of three ribosomal subunits (RLP 0, 2, and 3) known to be necessary for messenger RNA (mRNA) translation . Since mRNA translation occurs mainly in platelets that are a few hours old, one would expect to detect ribosomal P‐antigen in TO bright cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the results of MTT assays that suggest a role of uL3 in the cytotoxic activity of LQ1 led us to hypothesize that the activity of this ODN could be mediated by a nucleolar stress pathway involving uL3. To test this hypothesis, we analyzed the expression profile of uL3 and a subset of ribosomal proteins known to be involved in the nucleolar stress response, including uL5, uL11, uL18, uS12 [21,35,36], together with the nucleolar marker B23/NPM after treatment of the cells with LQ1. To this aim, HCT 116 p53−/− and uL3∆HCT 116 p53−/− cells were treated with 10 µM of LQ1, and, 48 h later, the relative abundance of uL3, uL5, uL11, uL18, uS12, and B23/NPM mRNAs was determined by RT-qPCR with specific primers ( Table 2).…”
Section: Lq1 Causes Nucleolar Stress and Affects Rrna Processingmentioning
confidence: 99%
“…Genetic manipulations were performed on a pEGFP-C1-uL10 plasmid described previously [45][46][47]. To obtain phospho-and dephosphomimetic variants of GFP-tagged uL10 protein, the pEGFP-C1-uL10 plasmid was mutated by replacing the TAT triplet coding Y24, the ACC triplet coding T59, or TCG coding S304 and S307 in the DNA sequence for the uL10 protein with GAA to obtain Y24E, T59E, and S304E/S307E (phosphomimetic) and with TTT, GCT, and GCG to obtain Y24F, T59A, and S304A/S307A (dephosphomimetic), respectively.…”
Section: Genetic Constructs and Site-directed Mutagenesismentioning
confidence: 99%